Does Perceived Effort Match Actual Measured Effort During Baseball Long Toss Programs?. Issue 7 (29th July 2019) - Melugin, Heath P.; Larson, Dirk; Fleisig, Glenn S.; Conte, Stan; Fealy, Stephen; Dines, Joshua S.; D'Angelo, John; Camp, Christopher L.
Objectives: Progressive throwing programs are a mainstay of rehabilitating the throwing athlete after injury or surgery. Athletes are commonly asked to throw at reduced levels of effort (i.e. "50% effort", "75%, " etc) to minimize stress to healing tissues. However, it is unknown whether players' perceived exertion matches actual exertion. The purpose of this study was to determine whether decreased effort correlates with decreased throwing metrics, whether metrics decrease to a predictable degree, and to quantify variability of these metrics within a given athlete when attempting to throw at sub-maximal effort. Methods: Sixty healthy, high school and collegiate baseball pitchers participated in a structured throwing program. After warming up, each pitcher was asked to throw five, max effort long toss throws at a distance of 120 feet. Afterwards, they were asked to give 5 throws at both 75% effort and 50% effort from the same distance. A motusBASEBALL sleeve (Motus Global, Inc.; Massapequa, NY) was worn by all players, which measured arm slot, velocity, shoulder rotation, and elbow varus torque (Nm). Ball velocity was measured in miles per hour (MPH) using a radar gun. The observed changes in throwing metrics were compared to one another across each of the throwing scenarios using a general estimating equation to control for multiple comparisons. They were also compared to the expected change to see if a decrease from 100% effort to 75%, and then to 50% resulted in proportional decreases in elbow torque and ball velocity. Intra-thrower variability was determined for each throwing metric at each degree of effort, and these results are reported using intra-class correlation coefficients (ICC) where an ICC > 0.75 was considered to represent excellent agreement. Results: Mean elbow torque decreased as players decreased their perceived effort from 100% (72.7 Nm) to 75% (67.3 Nm) to 50% (62.s Nm) (p<0.001). Mean ball velocity also decreased as they progressed from 100% effort (77.8 MPH) to 75% effort (66.5) to 50% effort (60.3 MPH) throws (p<0.001). However, these observed decreases in torque and velocity were much smaller in magnitude than the decreases in perceived effort. During the 75% effort throws, torque and velocity were not reduced to 75% of max. Instead, elbow torque was only reduced to 93.3% of max, and velocity dropped to 86.1% of max. Similarly, for the 50% effort throws, torque remained 86.5% of max effort torque, while velocity remained 78.1% of max. Accordingly, for every 25% decrease in perceived effort, torque only decreased 7%, and velocity only decreased 11%. These observed differences were all significantly different than the expected differences (p<0.001 for all). Intra-thrower reliability was considered excellent for all metrics within each throwing scenario: max effort, 75% effort, and 50% effort (ICC>0.75 for all). Conclusion: Measured effort was significantly greater than perceived effort during this standardized throwing program for all metrics tested. This is especially true for ball velocity and varus elbow torque. Ultimately, when players throw at what they perceive to be "reduced effort, " their actual throwing metrics do not decrease at the same rate as their perceived exertion. This has significant implications for throwers during the rehabilitation process as their elbows are likely experiencing more stress than desired. Clinicians and coaches must be aware and may want to consider transitioning to more objective measures of effort during rehabilition.